The addition of PD-1 inhibitor overcame trastuzumab resistance in patients with HER2 positive, PD-L1 negative metastatic gastric cancer: Case report and review of literature - Wen, Zhenpeng; Ye, Daoli; Hu, Qiancheng; Gou, Hongfeng (Frontiers in Pharmacology, 2024)
Gastric cancer (GC) is a malignancy with poor prognosis and high heterogeneity. For HER2-positive, PD-L1 negative metastatic GC patients, chemotherapy plus trastuzumab is the first-line therapy.However, those patients soon acquired resistance to treatment, especially to trastuzumab during the treatment. How to improve the therapeutic resistance of HER2-positive, PD-L1 negative metastatic GC is still a dilemma. We present the case of a metastatic GC patient with HER2 positive and PD-L1 negative expression who suffered progression after a short remission with trastuzumab plus chemotherapy. The patient exhibited a strong heterogeneity in the primary and metastatic lesions.His resistance to trastuzumab was overcome after the addition of a PD-1 inhibitor, then he received a durable response more than eight months. In HER2 positive, PD-L1 negative metastatic GC, the addition of PD-1 inhibitor after first-line chemotherapy and trastuzumab treatment resistance may be an option.